A antipedagogia de Tolstói na educação infantil - Camargo, Isabela Ferreira da Silva (Universidade Federal de São Carlos)
This final project focuses on the reflective exploration and research of the pedagogical experiences of Yasnaya Polyana, seeking to identify the aggregative and applicable possibilities that the pedagogical framework constructed by Tolstoy can offer to contemporary Brazilian early childhood education, with a view to enabling more humane and emancipatory teaching practices. The project employed a methodological bibliographic collection process of various textual genres, expanding the boundaries of traditional academic and scientific sources. The primary sources used were literary, didactic, religious, and other critical works by Tolstoy, in national and foreign languages, as well as those of commentators, who comprise a limited universe. The work concluded that Tolstoy and Russian education possess a rich historical and cultural heritage, whose analysis and reflection, especially on the experience developed in Yasnaya Polyana, can favor the development of new educational approaches and practices in our current reality.
Tolstoy's anti-pedagogy in early childhood education
La antipedagogía de Tolstói en la educación infantil
Keywords: Antipedagogia; Iasnaia Poliana; Tolstói; Anti-pedagogy; Iasnaia Poliana; Tolstoy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade